Keseimbangan Dinamis Berpengaruh terhadap Kemampuan Fungsional Activity of Daily Living pada Lansia - Heny Pramuta Sari; Katmini Katmini; Indasah Indasah; Agusta Dian Ellina (FORIKES, 2022)
Elderly is part of the growth and development process, which generally faces weaknesses, limitations, disabilities and decreased balance, which will affect the ability to walk, physical performance, quality of life and ability to do activities of daily living. This study aims to analyze the effect of static balance and dynamic balance on the functional ability of activity of daily living in the elderly. The research design is cross-sectional. Subjects are 37 elderly. They measured the level of static balance with the Stork Stand Test method, dynamic balance with the Time Up and Go method and the ability of activity of daily living by filling out the Barthel Index questionnaire. The results of the linearity test showed that the p-value for the static balance factor was 0.000, for the dynamic balance it was 0.126. The results of the t test for static balance show the value of p = 0.319, while for dynamic balance = 0.000. The results of the F test showed a value of p = 0.000. It can be interpreted that there is no effect of static balance on the functional ability of activities of daily living and there is an effect of dynamic balance on the functional ability of activity of daily living in the elderly.Keywords: elderly; static balance; dynamic balance; activity of daily living ABSTRAK Lanjut usia adalah bagian dari proses pertumbuhan dan perkembangan, yang pada umumnya menghadapi kelemahan, keterbatasan, ketidakmampuan dan penurunan keseimbangan, yang akan berpengaruh terhadap kemampuan berjalan, performa fisik, kualitas hidup dan kemampuan activity of daily living. Penelitian ini bertujuan untuk menganalisis pengaruh keseimbangan statis dan keseimbangan dinamis terhadap kemampuan fungsional activity of daily living pada lansia. Rancangan penelitian ini adalah cross-sectional. Subjek adalah 37 lansia. Pada mereka dilakukan pengukuran tingkat keseimbangan statis dengan metode Stork Stand Test, keseimbangan dinamis dengan metode Time Up and Go dan kemampuan activity of daily living dengan pengisian kuesioner Barthel Index. Hasil uji linearitas menunjukkan nilai p untuk faktor keseimbangan statis adalah 0,000, untuk keseimbangan dinamis adalah 0,126. Hasil uji t untuk keseimbangan statis menunjukkan nilai p = 0,319, sedangkan untuk keseimbangan dinamis = 0,000. Hasil uji F menunjukkan nilai p = 0,000. Dapat diinterpretasikan bahwa tidak ada pengaruh keseimbangan statis terhadap kemampuan fungsional activity of daily living dan ada pengaruh keseimbangan dinamis terhadap kemampuan fungsional activity of daily living pada lansia.Kata kunci: lansia; keseimbangan statis; keseimbangan dinamis; activity of daily living